Determination of Naphthalene Content by Gas Chromatography - Anjaneyulu, Y.; Marayya, R.; Linga Rao, D.; Krishna Rao, P. (Asian Journal of Chemistry, 2010)
A rapid and specific gas chromatographic analytical method is developed for detection and estimation of naphthalene in a complex matrix of potentially interfering substances, using a 5% SE-30 packed column, with a run time of 20 min. The detection level is established at 10 ppm.